The Implementation of Tolerance Education in Shaping Praiseworthy Morals at Taska Al-Fikh Orchard Ayer Tawar - Wardatun Ulfa; Zailani (Bulletin of Science Education, 2024)
The most crucial tool in the educational pillar of positive development efforts for children is tolerance education, which applies admirable moral values to them and helps them respect life's rules, including ethics and behavioral patterns. The purpose of this study is to describe how tolerance education is used in Taska Al-Fikh Orchard Ayer Tawar to develop admirable morals in those who are only focused on tolerance education. A qualitative descriptive approach is used in this study. Taska Al-Fikh Orchard in Ayer Tawar, Perak, Malaysia, was the site of this study. The study's findings demonstrate that the process of implementing tolerance education at Taska Al-Fikh Orchard Ayer Tawar through the development of admirable morals is evident in the focus on religious values, which are one of the triggers or values emphasized on moral relativism as a function in building moral leadership (discipline). Self) With Consequences for Four Characters: Religion, Responsibility, Respect, and Discipline as the Foundation for Students' Thoughts and Actions and as Reinforcement. Routine activities, spontaneous activities, planned activities, and examples that are carried out in a way that kids may observe the way educators or teachers set an example for kids by helping others in need around them are all ways that habits are formed.